Invasive group A Streptococcus resulting in sepsis and abdominal wall abscess after adenotonsillectomy. (1st November 2014) - Wilson, Paul F.; Wannemuehler, Todd J.; Matt, Bruce H.
<x xml:space="preserve">Abstract</x> Systemic infectious complications following adenotonsillectomy are exceedingly rare. We describe an otherwise healthy 2‐year‐old patient who developed group A beta‐hemolytic Streptococcus sepsis and presumptive scarlet fever 3 days after an uncomplicated adenotonsillectomy. After resolution of fever, rash, and discharge home on antibiotics, the patient returned on postoperative day 10 with an abdominal wall abscess. This is the first reported case of an abdominal wall abscess as a complication of adenotonsillectomy. This case demonstrates that an awareness of unexpected infectious complications of adenotonsillectomy should be a part of postsurgical management. Laryngoscope, 125:1230–1232, 2015